Early main-group metal catalysts for the hydrogenation of alkenes with H2 - Spielmann, Jan; Buch, Frank; Harder, Sjoerd (Angewandte Chemie International Edition, 2008)
(Chemical Equation Presented) Transition-metal-free hydrogenation of alkenes can be carried out with simple organocalcium catalysts (20 bar H , 20°C). Both steps in the proposed catalytic cycle, hydride addition to the double bond and σ-bond metathesis with H, have been confirmed. Alkenes sensitive to polymerization are also hydrogenated in good yields. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.